Penerapan Metode Activity Based Costing (ABC) Untuk Menentukan Harga Pokok Produksi Pada Usaha Pengolahan Sagu - Mulyaningsih, Sri; Mubarak, Husni (Politeknik Negeri Bengkalis, 2024)
The purpose of this research is to produce a more accurate estimate of the cost of goods manufactured by considering the activities involved in the sago production process. The type of data used is quantitative data obtained through secondary data, such as company history, organizational structure, and operational activities of the sago refinery. The data collection technique applied is documentation, with data processing using Activity Based Costing (ABC). Data analysis is done descriptively, describing the characteristics and patterns of the collected data. The results of this study indicate that overall the Activity Based Costing Method provides a lower value for the products produced, or in other words these two products experience overcosting. In the calculation of the cost of production of wet sago using the ABC method, the difference is Rp. 155.48 (44.20%) compared to using the traditional method used by the Selat Akar Village Sago Refinery.Â Meanwhile, in the calculation of the production cost of dry sago using the ABC method, the difference is Rp. 199.26 (55.80%). This proves that the Activity-Based Costing method is more accurate than the traditional method because in the Activity-Based Costing method, all factory overhead costs are calculated in detail based on activities, allowing the Sago Mill to determine the actual costs incurred in its production activities.Keywords: Activity Based Costing (ABC), Cost of Goods Produced.